Treating PTSD: A Review of Evidence-Based Psychotherapy Interventions - Watkins, Laura E.; Sprang, Kelsey R.; Rothbaum, Barbara O. (Frontiers in Behavioral Neuroscience, 2018)
Posttraumatic stress disorder (PTSD) is a chronic, often debilitating mental health disorder that may develop after a traumatic life event. Fortunately, effective psychological treatments for PTSD exist. In 2017, the Veterans Health Administration and Department of Defense and the American Psychological Association each published treatment guidelines for PTSD, which are a set of recommendations for providers who treat individuals with PTSD. The purpose of the current review is to briefly review the methodology used in each set of 2017 guidelines and then discuss the psychological treatments of PTSD for adults that were strongly recommended by both sets of guidelines. Both guidelines strongly recommended use of Prolonged Exposure, Cognitive Processing Therapy, and trauma-focused Cognitive Behavioral Therapy. Each of these treatments has a large evidence base and is trauma-focused, which means they directly address memories of the traumatic event or thoughts and feelings related to the traumatic event. Finally, we will discuss implications and future directions.